Structured Light Field Recovery from Dynamic Scattering Media - Shiwen Zhou; Guangcui Mo; Zepei Zeng; Yanwen Hu; Shenhe Fu (Photonics)
Performing light field recovery from diffusing wave is difficult owing to its complex and randomized light behaviors imposed by scatters. The problem becomes even more challenging when a time-varying scattering medium is involved, because, the scattered light changes in space and time. Here we report theoretically and experimentally an approach to structured field recovery behind a dynamic scattering medium, both in the near-field and the far-field diffraction regimes. We exploit the temporal irregular scattering behaviors of the dynamic scatter to overcome light field distortions, without any prior knowledge or wavefront control technique. Of particular interest is that the technique can work with a fast response rate of the scattering change in the order of microsecond level, which is inaccessible with previous techniques. Furthermore, we demonstrate the possibility for recovering a higher-order vector vortex light field from a dynamic diffuser, which was not addressed before. This work shows a significant advance toward light field recovery behind the dynamic scatters and may find intriguing applications.